2013
DOI: 10.1371/journal.pone.0067910
|View full text |Cite
|
Sign up to set email alerts
|

Retention in Care and Outpatient Costs for Children Receiving Antiretroviral Therapy in Zambia: A Retrospective Cohort Analysis

Abstract: BackgroundThere are few published estimates of the cost of pediatric antiretroviral therapy (ART) in Africa. Our objective was to estimate the outpatient cost of providing ART to children remaining in care at six public sector clinics in Zambia during the first three years after ART initiation, stratified by service delivery site and time on treatment.MethodsData on resource utilization (drugs, diagnostics, outpatient visits, fixed costs) and treatment outcomes (in care, died, lost to follow up) were extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Only one study from Zambia purposively selected 6 sites to represent different health facility levels. [ 20 ] Most sites from the included articles were public (government) facilities in urban areas. Detailed site information is available in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Only one study from Zambia purposively selected 6 sites to represent different health facility levels. [ 20 ] Most sites from the included articles were public (government) facilities in urban areas. Detailed site information is available in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Facility-based studies that estimated unit costs for pediatric HIV treatment found that they are often comparable to adult HIV treatment costs [ 73 ]. The average annual cost of providing ART to a child in Zambia was US$209 in 2011, ranging from US$116 to US$516 depending on site [ 59 ]. The cost is higher in South Africa: the first-year average cost per child in care and responding to treatment was US$830 at one site and US$678 at another [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we did not have detailed data for children in Côte d’Ivoire; we used clinical data from East and Southern Africa and varied only costs. Although our approach to deriving healthcare costs matched published economic data from South Africa and Zambia (a low-income country with GDP similar to Côte d’Ivoire), such an approach excluded country-specific factors, such as reduced malaria risk with protease inhibitors, which might change the clinical and cost-effectiveness of first-line lopinavir/ritonavir [ 36 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%